The Influence of Customer Value Co-Creation Behavior on Customer Value (Survey of Ruangguru Application Customers in Indonesia) - Mustika Ekawati; Andriani Kusumawati; Mohammad Iqbal (Wacana Journal of Social and Humanity Studies, 2022)
This research aims to determine and explain the effect of customer value co-creation behavior on customer value. This research is explanatory research using a quantitative approach. The questionnaires are used as a primary data collection to survey respondents directly. The population of this study is Ruangguru application customers who have been customers for at least one month. The location of this research is Ruangguru application customers in all cities in Indonesia. The sampling technique used was purposive sampling with a two-stage sampling method and obtained a total sample of 195 respondents. Data analysis was carried out Using SEM PLS and processed through the smartPLS 3.0 application and SPSS 24. This research shows that customer participation and citizenship behavior positively and significantly affect customer value. Customer citizenship behavior has the most dominant influence on customer value. Ruangguru customers find more value and benefits than expected when using Ruangguru Application with customer citizenship behavior. The findings of this research encourage managers of Ruangguru Application to formulate a strategy for customers to participate in the process of value co-creation so that Ruangguru Customers can act voluntarily to get better service. Keywords: customer value, value co-creation behaviour, participation behavior, citizenship behavior